2009
DOI: 10.1021/la8020244
|View full text |Cite
|
Sign up to set email alerts
|

Simple Phenomenological Model for Phase Transitions in Confined Geometry. 2. Capillary Condensation/Evaporation in Cylindrical Mesopores

Abstract: Abstract. A simple phenomenological model that describes capillary condensation and evaporation of pure fluids confined in cylindrical mesopores is presented. Following the work of Celestini (Phys. Lett. A, 1997, 228, 84), the free energy density of the system is derived using interfacial tensions and a corrective term that accounts for the interaction coupling between the vapor/adsorbed liquid and the adsorbed liquid/adsorbent interfaces. This corrective term is shown to be consistent with the Gibbs adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 64 publications
2
59
0
Order By: Relevance
“…3(a) and 3(b)]. The smaller width corresponds to what are also known in the literature as "intragranular" C─S─H layers [21], while a 1 nm distance between silicate-rich layers exceeds that expected for a C─S─H unit cell [39] and is termed "intergranular." However, our current definition of interlayer space as regions between silicate-rich layers that are smaller than a gel pore does not further distinguish between these two types of nanometerscale interlayer spaces when computing interlayer water content and its impact on isotherms or drying shrinkage.…”
Section: Interlayer Watermentioning
confidence: 86%
“…3(a) and 3(b)]. The smaller width corresponds to what are also known in the literature as "intragranular" C─S─H layers [21], while a 1 nm distance between silicate-rich layers exceeds that expected for a C─S─H unit cell [39] and is termed "intergranular." However, our current definition of interlayer space as regions between silicate-rich layers that are smaller than a gel pore does not further distinguish between these two types of nanometerscale interlayer spaces when computing interlayer water content and its impact on isotherms or drying shrinkage.…”
Section: Interlayer Watermentioning
confidence: 86%
“…For example, capillary critical temperatures in confined geometries are reported experimentally for SF 6 in porous glass and several gases in MCM-41 by Thommes et al 13 and Morishige Findenegg, 14 respectively; the shift in the critical temperature is found to have linear dependence on the inverse pore width. Numerous theoretical studies and molecular simulations including density function theory [15][16][17][18] and Monte Carlo ͑MC͒ simulations [19][20][21][22][23][24][25] were performed to understand capillary condensation. Vishnyakov et al 26 were the first to perform MC simulations systematically on carbon slit pores and studied the shift of the vapor-liquid critical point under confinement.…”
Section: Introductionmentioning
confidence: 99%
“…29 On the other hand, recent works on disordered and interconnected pores and narrow cylindrical pores have shown that capillary condensation cannot be considered as the first order transition, 30 which led to some debate. 16,17,23,31 The critical temperature estimation is an integral part in the calculation and understanding of phase equilibria, yet little work has been reported on the effect of fluid-fluid interaction range on phase equilibria and critical properties under confinement. In this sense, composite effects of variable pore size with variable interaction range are somewhat missed from the far-reaching comprehension on the vaporliquid critical temperature under confinement.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining drying process occurs with a much reduced shrinkage rate, but almost entirely via desaturation (e.g. Fredlund and Rahardjo 1993;Kodikara et al 2002;Pellenq et al 2009). …”
Section: Experimental Backroundmentioning
confidence: 99%